2019
DOI: 10.1177/0886260519836785
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in Identity Processes and Posttraumatic Growth: A Study of Victims of Intimate Partner Violence

Abstract: The purpose of this study was to explore the role of social support for posttraumatic growth (PTG) and identity processes in a sample of 217 women victims of intimate partner violence (IPV), recruited from women shelters, social support centers, and through counseling psychologists. The results of the study highlight the important role of social support in seeking positive personal resolutions after experiencing traumatic events of IPV. It indicates that social support, but not social nonsupport, predicts high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…Another limitation in our analysis was the lack of data for other potential confounders or modifiers of the associations between IPV and EC and depressive symptoms. For example, the model did not consider social support, which may buffer the effects of violence on depressive symptoms ( Zukauskiene et al, 2019 ). Other unmeasured variables that likely affect the association between violence and depressive symptoms is adverse childhood experiences and witnessing or experiencing violence in the childhood home.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation in our analysis was the lack of data for other potential confounders or modifiers of the associations between IPV and EC and depressive symptoms. For example, the model did not consider social support, which may buffer the effects of violence on depressive symptoms ( Zukauskiene et al, 2019 ). Other unmeasured variables that likely affect the association between violence and depressive symptoms is adverse childhood experiences and witnessing or experiencing violence in the childhood home.…”
Section: Discussionmentioning
confidence: 99%
“…Societal reactions to discrimination and violence can impact the mental health of individuals who are victimized and others. There is growing evidence that various forms of support provided by others, including a sensitivity to suffering, may help buffer negative mental health outcomes [ 43 , 44 ]. For example, Asians who experienced COVID-19-related discrimination reported fewer negative mental health outcomes when others provided emotional and social support [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is a great body of literature suggesting that traumatic experiences, despite their adverse content, may also foster some positive changes in life such as post-traumatic growth ( Tedeschi and Calhoun, 2004 ; Joseph et al, 2012 ), also among youth ( Mohr and Rosén, 2017 ). Moreover, it has been demonstrated that post-traumatic growth is positively linked to such positive identity processes as commitment making, identification with commitment, and exploration in breadth ( Žukauskienė et al, 2019 ). Similarly to the findings in adolescence, the results of our study support the idea that negative life experiences not necessarily result in negative outcomes in terms of identity development ( de Moor et al, 2019 ) and indicate that individual differences may occur when processing traumatic experiences, depending on different factors such as, for example, centrality of event ( Berntsen and Rubin, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shortened version of the scale includes 12 items, measuring five identity development processes: Exploration in Breadth (two items, e.g., “I am considering a number of different lifestyles that might suit me”), Commitment Making (two items, e.g., “I have decided on the direction I am going to follow in my life”), Exploration in Depth (three items, e.g., “I think about whether the aims I already have for life really suit me”), Identification with Commitment (two items, e.g., “My future plans give me self-confidence”), and Ruminative Exploration (three items, e.g., “I keep wondering which direction my life has to take”). Each item is evaluated on a 5-point Likert scale, ranging from (1) “completely disagree” to (5) “completely agree.” The Lithuanian version of shortened DIDS scale was previously used in other studies and its validity was established ( Žukauskienė et al, 2019 ). Confirmatory Factor Analysis (CFA) of a five-factor model also yielded a good model fit in our study [ χ 2 (44) = 359.878, p < 0.001, CFI/TLI = 0.952/.928, RMSEA (90% CI) = 0.067 (0.060, 0.073), SRMR = 0.054].…”
Section: Methodsmentioning
confidence: 99%